Twin Deficits through the Looking Glass: Time-Varying Analysis in the Euro Area - António Afonso; José Carlos Coelho (Center for Economic Studies and ifo Institute (CESifo), 2022)
Using two measures of the fiscal position, the cyclically adjusted primary budget balance (CAPB) and the total budget balance, we assess the Twin Deficit Hypothesis for the Euro Area in the period 1995-2020. Furthermore, we estimate time-varying coefficients of the current account balance responses to changes in the CAPB and in the government balance and we identify the determinants of these responses. The CAPB and the government balance, in addition to being determinants of the current account balance, are also determinants of the time-varying responses of the current account balance. The levels of government balance, current account balance and public debt, as a percentage of GDP, and the temporal period (before and after 2010) also influence these responses.
Keywords: F32; F41; H62; C33; 330; CAPB; government balance; current account balance; time-varying coefficients; Eurozone; panel data